2020
DOI: 10.1016/j.fertnstert.2019.10.018
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality from infancy to adolescence in singleton children conceived from assisted reproductive techniques versus naturally conceived singletons in Sweden

Abstract: Objective: To assess infant (<1 year) and childhood (1-18 years) mortality in singletons conceived through assisted reproductive techniques (ART) versus naturally conceived singletons. Design: Nationwide prospective study. Setting: Sweden. Patient(s): All singleton liveborn infants born from 1983 to 2012 in Sweden identified using the Medical Birth Register (N ¼ 2,847,108), of whom 43,506 were conceived through ART treatments including in vitro fertilization with and without intracytoplasmic sperm injection. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Whether the findings could be due to a beneficial causal effect or perhaps more plausibly unmeasured confounding, we note that they raise no concerns for the procedures’ potential influence on psychiatric health. In previous contrasts, frozen embryo transfer has appeared more favorable with respect to preterm birth and low birth weight, whereas a recent Swedish study found it associated with higher mortality in the first year of life. We note that as the technology has improved over time, with vitrification replacing slow freezing, so have the indications for use, with elective freeze-all for later transfer being advocated in specific clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the findings could be due to a beneficial causal effect or perhaps more plausibly unmeasured confounding, we note that they raise no concerns for the procedures’ potential influence on psychiatric health. In previous contrasts, frozen embryo transfer has appeared more favorable with respect to preterm birth and low birth weight, whereas a recent Swedish study found it associated with higher mortality in the first year of life. We note that as the technology has improved over time, with vitrification replacing slow freezing, so have the indications for use, with elective freeze-all for later transfer being advocated in specific clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…26 According to another study conducted in February 2020 higher risk for mortality can be seen in children who were conceived by the in vitro fertilization (IVF). 27 There is need to highlight the safety data both for mother and baby in ART among the gynecologist, so that they can better explain it to their patients. There must be more research particularly at local level so that they can better guide and reassure their patients regarding ART.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, for instance, population-based cohort research indicated a higher risk of preterm infant mortality from birth to one year of age in those born as a result of assisted reproductive technology compared with those conceived naturally. 2 As the authors noted, this was a retrospective study, so it is possible that crucial information was overlooked. Although numerous characteristics were given, this study did not focus on several important factors that influence the outcomes of extremely premature children.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%